PENAPISAN PERENCANAAN SISTEM PENYALURAN AIR LIMBAH DOMESTIK KECAMATAN BEJI, KOTA DEPOK - Albyant Sastra Wiguna; Eka Wardhani; Nico Halomoan (Universitas Kebangsaan, 2019)
One of the cities in West Java that is in dire need of attention on environmental problems is Depok City. Based on the Environmental Health Risk Assessment (EHRA) of Depok City of 2011, Kukusan Village, Beji Sub District is determined into the category of very high sanitation risk, for Kelurahan Pondok Cina, Bejitimur, and Tanah Baru is at the high risk on sanitation problems. The village of Beji and Kemirimuka is in the category of medium. In the year 2015 Beji District has 495 KK that still does not use toilets or latrines, 29 KK are still using insecure latrines, and 43,522 KK are already using a septic tank. On the update of the EHRA study , in reviewing from the time it takes of the manufacture and discharge of the septic tank. In 2015, Beji District had 29.66% that are already 5-10 years old, 42.90% had been more than 10 years, and 70.34% was never discharged. To overcome some of these problems it requires the construction of the domestic waste water management system or Sistem Pengelolaan Air Limbah Domestik (SPALD) with consideration of filtering according to the regulation of the Minister of Public Works and People's Housing Republic of Indonesia No. 4, 2017 on the implementation of domestic waste water management system. Based on the results of filtering, Beji subdistrict does not meet the requirements of the filtering of centralized domestic wastewater management system or Sistem Pengelolaan Air Limbah Domestik Terpusat (SPALD-T) according to regulations but there is quality improvements that makes Beji district can be considered for SPALD-T Keywords: Beji District, Screening, Domestic Wastewater Management System